Geotechnical characterization to determine the small-scale slope stabilization model - Blas Cano, Jaime Walter (2023)
The research analyzes the problem of instability of the slope of a critical section and develops a value on the slope of the Puente San Gerónimo - Puente Raymondi road section. The geotechnical characterization was carried out from in situ exploration, obtaining representative samples and laboratory tests to classify according to SUCS and ASHTO and the following was obtained: ϕ = 32.31° y c=17.65 kN/m2, specific weight = 16.97 kN/m3. From the stability analysis using the limit equilibrium method, the safety factors: for the natural slope FS=0.86 and for the stabilized slope FS=1.20.The research design is experimental. The development of the slope on a reduced scale for the natural slope and the stabilized slope was carried out for three specimens, in which the following were determined: forces, deformations and applied stresses; developing the comparative analysis of the slopes, such as the variation of the safety factors, variation of the load applied during the test, variation of the resistances, define the participation of efforts and similarities. Finally, it was obtained that the safety factor increased by 28.33% due to the proposal; which allows to contrast the research hypothesis.